“Калeвала”: деякі аспекти історичного та етнокультурного вивчення - Михайлова, Р. (Народна творчість та етнографія, 2005)
This article gives a brief history of “Kalevala” texts, its recording, publishing, structure and the meaning for the further development of epic traditions. The focus of this article is “mythic-sacral” character” of “Kalevala” texts. The author analyzing the rhythm, images, symbols and performing style of these texts brings the analogies from Slavic folk ritual and epic traditions. The author of the this paper looks at the “Kalevala” as “South-European bible”, which contains folk knowledge, experience, philosophy, etc. Those texts were very influential for the formation of some cultural traditions of the other European countries. The elements of the texts which show some connections with epos of some Germanic and Slavic cultures give an interesting material for contemporary comparative studies.